Cache na WWW: Limitações e Potencial - Murta, Cristina Duarte; Almeida, Virgílio A. F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
WWW caching systems are essential for Web performance and scalability. Web cache workloads and goals show important differences when compared with traditional caching systems, such as memory caches. This article points out and discusses these differences. In order to illustrate our discussion, we present characterization of ten workloads from Web caches. The analysis focuses on the parameters response size and access patterns. We discuss the influence of the characterized parameters in cache performance according to relevant metrics for the WWW and we show directions for the design of Web cache replacement policies.